Inflammatory myofibroblastic tumor of the spleen: a case report - H. Bettach; B. Alami; M. Boubbou; L. Chbani; M. Maâroufi; MY Alaoui Lamrani (Radiology Case Reports, 2021)
Inflammatory myofibroblastic tumors (IMTs), otherwise known as the inflammatory pseudotumor, is a rare solid mesenchymal tumor, simulating malignant neoplasms, histologically characterized by the proliferation of spindle cells in a fibrous myxoid stroma containing inflammatory cells. CT and MR imaging are the most used tools in their assessment. Clinical features are nonspecific and depend on the localization of the tumor, radiologic findings are polymorphic and no-conclusive and present a diagnostic challenge to the radiologist. Although histology remains obligatory for the final diagnosis. Heren, we report a case of splenic IMT with histological correlation.